Notoginsenoside R1 Ameliorates Cardiac Lipotoxicity Through AMPK Signaling Pathway - Tian, Xue; Chen, Xu; Jiang, Qianqian; Sun, Qianbin; Liu, Tiantian; Hong, Yiqin; Zhang, Yawen; Jiang, Yanyan; Shao, Mingyan; Yang, Ran; Li, Chun; Wang, Qiyan; et al. (Frontiers in Pharmacology, 2022)
Aims: Cardiac lipotoxicity is the common consequence of lipid metabolism disorders in cardiomyocytes during development of heart failure (HF). Adenosine 5′monophosphate-activated protein kinase (AMPK) acts as an energy sensor and has a beneficial effect in reducing lipotoxicity. Notoginsenoside R1(NGR1) is extracted from the traditional Chinese medicine Panax notoginseng (Burkill) F.H.Chen (P. notoginseng) and has definite cardioprotective effects. However, whether NGR1 can attenuate HF by mitigating lipotoxicity has not been elucidated yet. This study aimed to explore whether NGR1 plays a protective role against HF by ameliorating cardiac lipotoxicity via the AMPK pathway. Materials and Methods: HF mice model was established by left anterior descending ligation. Palmitic acid (PA) stimulated H9C2 cell model was applied to clarify the effects and potential mechanism of NGR1 on lipotoxicity. In vivo, NGR1 (7.14mg/kg) were orally administered for 14 days and simvastatin (2.9 mg/kg) was selected as a positive drug. Echocardiography was applied to assess heart functions. Lipid levels were measured by Enzyme-linked immunosorbent assay (ELISA). Key proteins in the AMPK pathway were detected by western blots. In vitro, NGR1 (40 μM) or Compound C (an inhibitor of AMPK, 10 μM) was co-cultured with PA stimulation for 24h in H9C2 cells. Results: NGR1 could significantly improve the cardiac function and myocardial injury in mice with HF and up-regulate the expression of p-AMPK. Impressively, NGR1 inhibited the synthesis of diacylglycerol (DAG) and ceramide and promoted fatty acid oxidation (FAO) in vivo. Moreover, NGR1 significantly promoted expression of CPT-1A, the key enzyme in FAO pathway, and down-regulated the expression of GPAT and SPT, which were the key enzymes catalyzing production of DAG and ceramide. Expression of phosphorylated AMPK was also upregulated by NGR1. In vitro experiments showed that NGR1 could significantly attenuate lipid accumulation in PA-induced H9C2 cells. Furthermore, co-treatment with inhibitor of AMPK abrogated the protective effects of NGR1. The regulative effects of NGR1 on lipid metabolism were also reversed by AMPK inhibitor. Conclusion: NGR1 could significantly improve the heart function of mice with HF and reduce cardiac lipotoxicity. The cardio-protective effects are mediated by the activation of AMPK pathway.